2020
DOI: 10.1029/2019jb018313
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inversion of Wrapped Satellite Interferometric Phase to Estimate Fault and Volcano Surface Ground Deformation Models

Abstract: Bayesian inference and an improved downsampling method is used to determine earthquake and volcano source parameters using a popular geodetic observation method, satellite radar interferometry. The main novelty of the proposed approach is that the interferometric wrapped phase can be directly inverted, circumventing the ill‐posed phase unwrapping processing step. Phase unwrapping errors severely affect the estimation of earthquake and volcano source parameters using interferometric observations. Therefore, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…To develop the kinematic fault model, we first constructed the fault geometry derived from a nonlinear fault inversion of InSAR wrapped phase observations, solving for uniform distribution on rectangular faults (Jiang & González, 2020). A geodetic inversion directly using the interferometric wrapped phase avoids any potential phase unwrapping error (Figure S6 in Supporting Information S1).…”
Section: Spatio-temporal Slip Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…To develop the kinematic fault model, we first constructed the fault geometry derived from a nonlinear fault inversion of InSAR wrapped phase observations, solving for uniform distribution on rectangular faults (Jiang & González, 2020). A geodetic inversion directly using the interferometric wrapped phase avoids any potential phase unwrapping error (Figure S6 in Supporting Information S1).…”
Section: Spatio-temporal Slip Evolutionmentioning
confidence: 99%
“…A geodetic inversion directly using the interferometric wrapped phase avoids any potential phase unwrapping error (Figure S6 in Supporting Information S1). The data variance-covariances describing the noise level are calculated based on the covariograms (Figure S7 in Supporting Information S1) and are used to weight the wrapped phase residuals in the likelihood function as illustrated by Jiang and González (2020). Modeling of a selection of interferograms covering the successive phases confirmed that ground motion could be caused by fault geometry with two distinct planes.…”
Section: Spatio-temporal Slip Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…S12) due to the dense gradient of fringes. Instead, our method skips the phase unwrapping step, and directly inverts for fault source parameters by applying the WGBIS method, a Bayesian algorithm that minimizes the weighted wrapped phase residuals (Jiang and González, 2020). Now, using the wrapped InSAR phase and GNSS offsets, we can constrain more tightly the fault geometry parameters (Fig.…”
Section: Fault Geometry: Non-linear Surface Displacement Inversionmentioning
confidence: 99%
“…The earthquakes ruptured an area off the Alaska Peninsula covered with scattered islands, and incoherence due to water channels makes it challenging to estimate phase ambiguities during the InSAR phase unwrapping process. Hence, we take advantage of an improved Bayesian inversion of wrapped interferometric phase change observations (Jiang and González, 2020) to estimate the fault geometry and slip distribution. Our coseismic geodetic inversion results reveal that the Alaska megathrust has a complex down-dip segmentation.…”
Section: Introductionmentioning
confidence: 99%